Synergistic Protection of Retinal Ganglion Cells (RGCs) by SARM1 Inactivation with CNTF in a Rodent Model of Nonarteritic Anterior Ischemic Optic Neuropathy - Yan Guo; Zara Mehrabian; Jeffrey Milbrandt; Aaron DiAntonio; Steven L. Bernstein (Cells, 2024)
We evaluated whether inhibiting sterile alpha and (Toll/interleukin receptor (TIR)) motif-containing 1 (SARM1) activity protects retinal ganglion cells (RGCs) following ischemic axonopathy (rodent nonarteritic anterior ischemic optic neuropathy: rNAION) by itself and combined with ciliary neurotrophic factor (CNTF). Genetically modified SARM1(−) rats were rNAION-induced in one eye and compared against equivalently induced wild-type animals of the same background. Optic nerve (ON) diameters were quantified using optical coherence tomography (SD-OCT). RGCs were quantified 30 d post-induction using retinal stereology for Brn3a(+) nuclei. ON sections were analyzed by TEM and immunohistochemistry. SARM1(−)(−) and WT animals were then bilaterally sequentially rNAION-induced. One eye received intravitreal vehicle injection following induction; the contralateral side received CNTF and was analyzed 30 d post-induction. Inhibiting SARM1 activity suppressed axonal collapse following ischemic axonopathy. SARM1(−) animals significantly reduced RGC loss, compared with WT animals (49.4 ± 6.8% RGC loss in SARM1(−) vs. 63.6 ± 3.2% sem RGC loss in WT; Mann–Whitney one-tailed U-test, (p = 0.049)). IVT-CNTF treatment vs. IVT-vehicle in SARM1(−) animals further reduced RGC loss by 24% at 30 d post-induction, but CNTF did not, by itself, improve long-term RGC survival in WT animals compared with vehicle (Mann–Whitney one-tailed t-test; p = 0.033). While inhibiting SARM1 activity is itself neuroprotective, combining SARM1 inhibition and CNTF treatment generated a long-term, synergistic neuroprotective effect in ischemic neuropathy. Combinatorial treatments for NAION utilizing independent neuroprotective mechanisms may thus provide a greater effect than individual treatment modalities.